Forms of Internal Migrants’ Adjustment to Traditional Village Life in the Touristic Area of South Kuta, Bali - I Made Sarmita; Agus Joko Pitoyo; Sri Rum Giyarsih (Universitas Udayana, 2025)
The increasing flow of internal migrants to Bali has created social and cultural tensions within traditional village communities that uphold Hindu customary systems. This study examines how migrants adjust within the framework of Tri Hita Karana (Parhyangan, Pawongan, and Palemahan). The touristic villages of Jimbaran and Pecatu in South Kuta were selected because both continuously record positive net migration yet show contrasting cultural responses: Jimbaran, as an urban village, is generally more open and adaptive, while rural Pecatu maintains a more conservative orientation, producing different patterns of interaction and occasional tensions. Using a descriptive mixed-method approach, data were collected from 386 respondents across the two villages. The findings show that Krama Tamiu migrants (Balinese Hindus) adapt more easily due to shared religious values, while Tamiu migrants (non-Hindus) face greater barriers, particularly in spiritual participation. Participation levels are higher in Jimbaran, reflecting its more inclusive structure of the urban context. The study links Tri Hita Karana with social capital and acculturation to explain migrant integration.